Electrode substrate innovation for electrochemical detection in microchip electrophoresis. Issue 16 (19th August 2015) - Randviir, Edward P.; Banks, Craig E.
Abstract : Microchip electrophoresis (MCE) represents the next generation of miniaturised electrophoretic devices and carry benefits such as significant improvement in analysis times, lower consumption of reagents and samples, flexibility and procedural simplicity. The devices provide a separation method for complex sample matrices and an on‐board detection method for the analytical determination of a target compound. The detection part of MCE is increasingly leaning towards electrochemical methods, thus the selectivity and sensitivity of detection in MCE is dependent upon the chosen working electrode composition in addition to operating conditions of the chip such as separation voltage. Given the current plethora of electrode materials that are available, there exists a possibility to creatively integrate electrodes into MCE. This review will overview the application of several electrode materials, from the old through to the new. A particular recent focus has been the selectivity element of MCEs overcome with the use of enzymes, carbon composites and screen‐printed technologies.